The effect of supplemental irrigation from polyacrylamide-treated microcatchments on the growth of acacia saligna in dryland - Al-Mefleh, Naji K.; Tadros, Maher; Abu-Zreig, Majed M. (Forest science and technology, 2019)
A field study was carried to determine the impact of the land application of polyacrylamide (PAM) on the runoff used for supplemental irrigation. Five treatments were investigated: PAM A-130, PAM A-836, PAM Aerotil, plastic mulch, and natural (no PAM no mulch). Runoff was collected in barrels placed at the downstream end of fifteen plots and then used for the irrigation of acacia trees planted in an experimental site in Jordan. The growth characteristics of the acacia were monitored over a two-year period from 2009 to 2010. The total runoff volumes were significantly different over PAM A-836, PAM Aerotil, and plastic mulch compared to the natural. The results showed that supplemental irrigation of acacia with water collected from PAM plots significantly increased the acacia height and number of leaves compared to the natural and rainfed treatments. The use of PAM-treated runoff also slightly increased the number of branches of the acacia, but the increase was only significant in the case of PAM A-836. There was a weak correlation between the volume of supplemental irrigation generated and the morphological characteristics. The type of PAM seems to have improved plant growth irrespective of the volume of runoff collected.